Oral Hygiene Awarness Among The Primary School Childrenin A Rural Areaof Bangladesh - Karim, Farzana (International Journal of Human and Health Sciences (IJHHS), 2018)
Background: Now-a-days dental problem is one of the most common diseases in the world.Proper oral hygiene practicingin a regular basis are great ways to prevention of dental disease. Methodology: This cross sectional study was carried out with a view to assess the oral hygiene awareness among the primary school children of a rural area under Dhaka division of Bangladesh. Data about oral hygiene related knowledge and practices were collected by face to face interview of the children. Oral examination was done by disposable dental mirror and probe under sufficient light. Data were analyzed using SPSS version 16. Results: Among the 114 respondents 53.51% are male and rest are female. Age range of the respondents were 6 to 11 years.Oral hygiene related knowledge: Among the respondents 78.07% told that regularteeth cleaning is important,60.52% respondents told that teeth should be cleaned once daily,62.29% told that teeth should be cleaned by tooth brush and tooth paste,70.17% told that teeth should be cleaned before breakfast. Oral hygienerelated practice: Among 114 respondents 64.04% cleaned their teeth everyday,51.75%used tooth paste and toothbrush to clean their teeth, 38.60%respondents cleaned their teeth in their convenient time. Among the tooth brush users, most of them changed their toothbrush when it was damaged or lost. All the respondents used match stick or coconut leaf stick if food was deposited in between their teeth. Oral hygiene status: Among the respondents 68.32 % had caries in their mouth. About 53.42% caries found in the lower jaw. Caries were more prevalent in molar teeth. About 69.34% respondents had plaque or calculus, 46.54% experienced gingival bleeding. Conclusion: Oral hygiene awareness among the respondents were very low. International Journal of Human and Health Sciences Vol. 01 No. 02 July’17. Page : 79-82